Evaluation of thermoregulation of horses (Equus caballus) submitted to two methods of post-exercise cooling, in hot and humid climate conditions, in the Eastern Amazon - Lisboa, Bruna Rafaela Ferreira; Silva, Jamile Andréa Rodrigues da; Silva, Welligton Conceição da; Barbosa, Antônio Vinícius Corrêa; Silva, Lilian Kátia Ximenes; Lourenço-Júnior, José de Brito (Frontiers in Veterinary Science, 2023)
In Brazil, the study on equine thermoregulation has not shown considerable advances, moreover, in the Amazon, this is a little explored aspect. This study aims to evaluate the thermoregulation of horses submitted to two methods of post-exercise cooling, in the climatic conditions of the Eastern Amazon. The experiment was conducted at Centro Hipico, Ananindeua, Para, for 15 days. Ten male horses, castrated of the Brazilian breed, aged 13 years and with an average weight of 482.3 kg were used. Equestrianism, which was exercised with pre-established protocol in the arena and track, for 30 min. After the exercise, the animals were divided into two groups for application of the treatments, which were two cooling methods, such as a bath with water at room temperature (about 25°C) and a hiper cooling method (6–9°C). During the experimental period, air temperature (AT) and relative humidity (RH) data were recorded and the Temperature and Humidity Index (THI) was calculated. Data from the rectal temperature (RT), heart rate (HR), respiratory rate (RR) and Body surface temperature (BST) of the animals were also measured at three moments: before exercise, after exercise and after applying the cooling methods. The adaptability index used was the Benezra Thermal Comfort Index (BTCI). The BST was performed with the help of infrared thermograph, which were the left side of the neck, thorax, rump, and right side to the armpi, before the exercise, after the exercise and after applying the cooling methods. The statistical design was completely randomized. Analysis of variance was performed using the GLM Procedure of SAS 9.1.3. After the application of the cooling techniques in the animals, the AT and THI were higher and the highest RH values were found before the exercise (87.21%). The highest RT, RR, HR, BST, and BTCI values were observed after exercise. There was no significant dierence (P > 0.05) between cooling methods. There was a highly significant and positive correlation (P < 0.01) between all physiological variables (RT, RR, HR, and BST) and the Iberian Index with AT and THI and negative with RH (P < 0.01), thus demonstrating the influence of the environment on the thermoregulation of animals. It is concluded the evaluation of stress, welfare and thermoregulation of horses submitted to two methods of post-exercise cooling, in the climatic conditions of the Eastern Amazon, demonstrated that the studied cooling methods showed to reduce the rectal temperature, the respiratory rate, the heart rate and the body surface temperature with equal efficiency. However, in terms of practical ease of use, the room temperature water cooling method has proven to be more practical.